Draft genome sequence of a co-harbouring blaNDM-5 and mcr-1.1 Escherichia coli phylogroup A isolate associated with patient colonisation in Ireland - Anna Tumeo; Francesca McDonagh; Aneta Kovarova; Kate Ryan; Christina Clarke; Georgios Miliotis (Journal of Global Antimicrobial Resistance)
Objectives: While Escherichia coli phylogroup-A is typically associated with commensal strains, some isolates can harbour virulence and exhibit multidrug-resistant (MDR) phenotypes. We report the draft genome of a rare instance of carbapenem, fosfomycin and colistin resistant E. coli phylogroup-A, isolated as part of routine screening of a human patient in a clinical setting in Ireland. Methods: E. coli E230738 was identified using MALDI-ToF/MS. Antibiotic susceptibility testing was performed using the Sensititre-EUMDRXXF plate. Whole-genome-sequencing was conducted with NextSeq1000, and genomic analysis identified antibiotic-resistance-genes (ARGs) and virulence-factors (VFs). Phylogenetic analysis was performed using whole-genome-multilocus-sequence-typing (wgMLST). Results: E. coli E230738 genome was identified to belong to phylogroup-A/ST10 complex and to harbour 63 ARGs, 17 of which acquired. Resistance to beta-lactams, including carbapenems and cephalosporins was likely due to chromosomally identified blaNDM-5. Colistin resistance appeared associated with acquired mcr-1.1. Despite lacking fosfomycin-inactivating-enzymes, fosfomycin resistance was observed, possibly due to efflux pumps. Forty-seven chromosomal VFs were identified, involved in adhesion and iron acquisition amongst other properties. Plasmid replicons associated with the spread of MDR genes such as IncHI2/HI2A were detected. wgMLST analysis showed the closest relative being a strain from the UK, exhibiting differences in the sequences of 851 genes. Conclusion: This is a first detected instance of a blaNDM-5 and mcr-1.1 co-occurring in E. coli in Ireland. The MDR profile of E. coli E230738 highlights the growing public health concern posed by the dissemination of MDR E. coli lineages with limited treatment options and underscores the need for clinical screening coupled with genomic surveillance to better understand evolving MDR patterns in E. coli.